2019
DOI: 10.13057/biodiv/d200542
|View full text |Cite
|
Sign up to set email alerts
|

Using the modern morphometric approach to determine sexual dimorphism of three medically important flies (Order: Diptera) in Thailand

Abstract: Abstract. Chaiphongpachara T, Laojun S. 2019. Using the modern morphometric approach to determine sexual dimorphism of three medically important flies (Order: Diptera) in Thailand. Biodiversitas 20: 1482-1486.  This study assessed landmark-based geometric morphometric (GM) approach to determine sexual dimorphism of three medically important flies in Thailand, Chrysomya megacephala (Fabricius), Musca domestica (Linnaeus) and Boettcherisca nathani (Lopes). In the wing size analysis, the centroid size (CS) was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The geometric morphometric study was carried out to compare the wing size and wing shape between sexes of H. aberrans . Landmark-based geometric morphometrics has been mostly used in sexual dimorphism studies [ 32 , 33 , 36 ]. In the present study, we revealed a sexual dimorphism in wing shape, indicating that the phenotypic expression of wing shape is a sex-specific difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometric morphometric study was carried out to compare the wing size and wing shape between sexes of H. aberrans . Landmark-based geometric morphometrics has been mostly used in sexual dimorphism studies [ 32 , 33 , 36 ]. In the present study, we revealed a sexual dimorphism in wing shape, indicating that the phenotypic expression of wing shape is a sex-specific difference.…”
Section: Discussionmentioning
confidence: 99%
“…The landmark-based method uses the coordinates of landmarks to analyse the variation in size and shape, while the outline-based method uses the outline or contour data in the analysis [ 25 , 31 ]. Many studies have used geometric morphometric methods for describing sexual dimorphism in the wing of various insects such as blow flies [ 28 , 32 ], mosquitoes [ 33 , 34 ], moths [ 35 , 36 ], fruit flies [ 37 ] and stomoxyine flies [ 26 ]. Sexual dimorphism in morphological characters is the most interesting source of phenotypic variation in various taxa and has attracted considerable interest in evolutionary biology [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of houseflies as mechanical vectors for several diarrhea-causing agents is relatively well-established [3], [6], [12], [13], [14], [15]. The housefly, Musca domestica L. (Diptera: Muscidae), is a vector for over 100 serious pathogens, including typhoid, cholera, salmonellosis, shigellosis, dysentery, anthrax, and parasitic worms [3], [16], [17], [18], [19], [20], [21].…”
Section: Introductionmentioning
confidence: 99%